2014
DOI: 10.1016/j.jobcr.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of different intrusion methods and their effect on maxillary incisors

Abstract: a b s t r a c tIntroduction: To evaluate and compare the rate of intrusion and root resorption of maxillary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
0
6
1
3
Order By: Relevance
“…Our results showed that overall root resorption was 2.15 ± 0.85 mm with no statistically significant differences between the two groups. Other studies of incisor intrusion have obtained lower root resorption values when using miniscrews [7,19,31] or conventional intrusion archwires [14,32,33]. These differences may be due to the amount of intrusion produced, as there is a positive correlation between intrusion and resorption rates, as the present study demonstrates, the amount of intrusion found in the present study being higher than amounts reported in other studies (3.84 ± 2.96 mm).…”
Section: Discussioncontrasting
confidence: 64%
“…Our results showed that overall root resorption was 2.15 ± 0.85 mm with no statistically significant differences between the two groups. Other studies of incisor intrusion have obtained lower root resorption values when using miniscrews [7,19,31] or conventional intrusion archwires [14,32,33]. These differences may be due to the amount of intrusion produced, as there is a positive correlation between intrusion and resorption rates, as the present study demonstrates, the amount of intrusion found in the present study being higher than amounts reported in other studies (3.84 ± 2.96 mm).…”
Section: Discussioncontrasting
confidence: 64%
“…In previous studies of root resorption occurring during maxillary incisor intrusion obtained with conventional methods and screened with periapical X-rays, resorption varied between 0.6 mm and 2.5 mm. [16][17][18][19][20] Using utility arches, McFadden et al 18 found 0.84 mm of intrusion but 1.84 mm of resorption after termination of treatment (28.8 6 7.4 months); Goel et al 19 observed 1.56 mm of root shortening for 1.60 mm of intrusion during a 4.32-month period. Using a Burstone intrusion arch, Costopoulos and Nanda 16 observed 0.6 mm of resorption after 1.9 mm of apical movement of C R over 4.6 months with intrusive forces of 15 g per teeth.…”
Section: Anterior Vs Posterior Mini-implant-assisted Incisor Intrusionmentioning
confidence: 99%
“…8 Thus, effective incisor intrusion mechanics could be performed. 9 In addition, miniscrews are well established in the literature as an excellent source for anchorage reinforcement with high rates of success and low frequencies of adverse effects. 10 Consequently, identifying the plausible effects of miniscrews and other different intrusive mechanics would be of pronounced importance to clinicians.…”
Section: Introductionmentioning
confidence: 99%